Venlafaxine Attenuated the Cognitive and Memory Deficit in Mice Exposed to Isoflurane Alone - Li, Liang; Zhang, Chunhai (Frontiers in Neurology, 2021)
Postoperative cognitive dysfunction (POCD) is a common complication during the post-operative period. It affects the recovery time of patient after surgery and the stay time in hospital, which cause a great deal of burden to patients and families emotionally and financially. However, there is no specific and effective treatment available for this disorder. Recent study indicated exposure to general anesthetics contributes to POCD by triggering GABAA receptors hyperactivities that persisted even the anesthetic compounds have been eliminated. Here, we investigated the antidepressant, venlafaxine (VLX), in a mouse model of POCD, and studied whether VLX attenuated the cognitive dysfunction of mice exposed to general anesthetic, isoflurane (ISO). We found ISO significantly induced an increased surface expression of the GABAA receptor subunit, α5, in the hippocampus of the mice. However, VLX treatment reduced the increase of α5 subunit expression. Meanwhile, we found the expression levels of IL-1β, TNF-α and IL-6 in the mice exposed to ISO were significantly increased, however, which VLX prevented the increase of these cytokines in mouse brain. We also investigated the memory deficit of these mice by using a Y maze behavioral test. Mice with ISO exposure showed decreased alternation performance that was prevented by the VLX treatment. Collectively, our results here are in line with the previous findings that α5 subunit plays an important role of the formation of POCD but VLX may be a promising candidate compound for the treatment of POCD.